PELESTARIAN TARIAN BON MAYU PADA MASYARAKAT DESA WERE KECAMATAN WEDA KABUPATEN HALMAHERA TENGAH - Fajar Aprianto (HOLISTIK, Journal of Social and Culture, 2023)
One of the various art forms is dance. The existing dances have different backgrounds , according to the natural, social and cultural conditions in which they develop. For example , there are ritual dances that are sacred and religious, there are dances that are entertainment, there are dances that are social, and so on. Dance is also a system of knowledge, beliefs, values, products that grow and are shared by a community group . One of them is the Bon Mayu dance from Were Village, Weda District, Central Halmahera Regency. Bon Mayu dance itself is just like other folk dances, appreciating culture in general and following the norms outlined by customs, various movements reflect the subtlety of mind and character of the supporting community which is an integral part of oneself and the environment in which the dance develops born from historical ideas, activities and symbols . However, along with the development of the times, the flow of globalization is present and cannot be prevented from its presence, making cultural changes occur in traditional societies. Socio-cultural changes that occur result in human habits that are influenced by the needs of life and ways of thinking, so that change is the background of changing a dance presentation in a different direction. However, it is also caused by external factors and internal factors, some are changing towards the development of types of dance, there are also changes in the creativity strategy of presentation, this is due to the entry of modern technological elements that are more dominant, but it also depends on the background and environment of the community where the culture or art develops. Keywords: dance art, preservation, Bon Mayu